Implementation Analytical Hierarchy Process On Airplane Ticket Booking Application Selection With Software Quality Requirements and Evaluation ISO/IEC 25010:2011 - Fanny Andalia (Universitas Multimedia Nusantara, 2017)
Decision-making is the process of selecting alternative actions to achieve a particular goal. Increased movement of the number of passengers using air transportation mode, making the growth of ticket booking application also increase. A system judgment is required to determine which airplane ticket booking application to use. This study discusses the process of choosing an airplane ticket booking application using Analytical Hierarchy Process (AHP) method by using Systems and Software Quality Requirements and Evaluation ISO / IEC 25010:2011 criteria measurement of quality in use. The processed data is obtained from the geometric average of three respondents ie representatives from information technology experts, the public and travel agent. Analysis and data processing using expert choice tools. There are 3 applications airplane ticket booking online in this research deliberately disguised his name. This is because it is feared to have a negative effect on the existing business competition. The results obtained from this study that the application of ticket booking that have the highest value recommended for use is Application A, followed by Application B and Application C